2012
DOI: 10.2460/ajvr.73.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors associated with the risk of infection with Cryptosporidium parvum in dairy calves

Abstract: Risk factors for calf infection with C. parvum differed from those for infection with C. bovis. Results may be useful to help design measures that reduce animal exposure and decrease public health risk and economic losses associated with C. parvum infection in cattle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Breed type was previously proposed as a factor associated with infection of C. parvum. In a study of 391 experimentally infected dairy calves, the Jersey breed was identified as a risk factor for infection by C. bovis (Szonyi et al, 2012). In a cross-sectional study of 115 positive fecal samples from dairy cattle in New York State, Holstein calves were identified as more likely to be infected with C. parvum (Starkey et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Breed type was previously proposed as a factor associated with infection of C. parvum. In a study of 391 experimentally infected dairy calves, the Jersey breed was identified as a risk factor for infection by C. bovis (Szonyi et al, 2012). In a cross-sectional study of 115 positive fecal samples from dairy cattle in New York State, Holstein calves were identified as more likely to be infected with C. parvum (Starkey et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with a decreased risk of infection in preweaning calves were shown to be ventilation of calf rearing areas, daily addition of bedding, feeding of milk replacer, daily disposal and cleaning of bedding and the use of antibiotics. In addition, postweaning movement of animals was also associated with a decreased risk of infection with C. parvum (Wyatt et al, 2010;Szonyi et al, 2012).…”
Section: Enteric Diseasementioning
confidence: 99%
“…Since severity and incidence of clinical disease in infected calves is very inconsistent within and between farms, there are some authors that question if C. parvum is really a primary pathogen (Foster and Smith, 2009). The risk of clinical disease increases when animals are grouped together and when hygiene and management practices are deficient (TrotzWilliams et al, 2007;Szonyi et al, 2012). Factors associated with a decreased risk of infection in preweaning calves were shown to be ventilation of calf rearing areas, daily addition of bedding, feeding of milk replacer, daily disposal and cleaning of bedding and the use of antibiotics.…”
Section: Enteric Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Six studies considered whether certain breeds were more vulnerable to infection, of which one study (Imre et al 2015) found that 'pure-bred' animals (pure versus cross breed not defined) were at higher risk than cross breeds. Three studies (Maddox-Hyttel et al 2006;Szonyi et al 2012;Urie et al 2018) considered breed as a risk factor (Holsteins vs. Jerseys) and found that it did not matter. There is no clear support for significant differences in susceptibility to C. parvum between the major breeds of dairy cattle.…”
Section: Breedmentioning
confidence: 99%